„Slavica Revalensia”: Указатель содержания (2014—2023) [_Slavica Revalensia_: An Index to Past Volumes (2014—2023)] - Utgof, Grigori (Slavica Revalensia, 2026)
What awaits the reader in this section is an index to the content of Slavica Revalensia, the multilingual journal in Russian and Slavic Studies published since 2014 by Tallinn University Press.